Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài giải
\(\left|3x-5\right|+\left(2y+5\right)^{2008}+\left(4z-3\right)^{2006}\le0\)
Mà \(\hept{\begin{cases}\left|3x-5\right|\ge0\\\left(2y+5\right)^{2008}\ge0\\\left(4z-3\right)^{2006}\ge0\end{cases}}\) \(\Rightarrow\) Chỉ xảy ra trường hợp : \(\left|3x-5\right|+\left(2y+5\right)^{2008}+\left(4z-3\right)^{2006}=0\)
\(\Rightarrow\hept{\begin{cases}\left|3x-5\right|=0\\\left(2y+5\right)^{2008}=0\\\left(4z-3\right)^{2006}=0\end{cases}}\) \(\Rightarrow\hept{\begin{cases}3x-5=0\\2y+5=0\\4z-3=0\end{cases}}\) \(\Rightarrow\hept{\begin{cases}3x=5\\2y=-5\\4z=3\end{cases}}\) \(\Rightarrow\hept{\begin{cases}x=\frac{5}{3}\\y=-\frac{5}{2}\\x=\frac{3}{4}\end{cases}}\)
\(\Rightarrow\text{ }x=\frac{5}{3}\text{ , }y=-\frac{5}{2}\text{ , }z=\frac{3}{4}\)
Vì \(\left|\left|3x-3\right|+2x+\left(-1\right)^{2016}\right|\ge0\forall x\)
\(\Rightarrow3x+2017^0\ge0\Rightarrow x\ge-\frac{1}{3}\)
Khi đó: \(\left|\left|3x-3\right|+2x+1\right|=3x+1\)
\(\Leftrightarrow\orbr{\begin{cases}\left|3x-3\right|+2x+1=3x+1\\\left|3x-3\right|+2x+1=-3x-1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}\left|3x-3\right|=x\\\left|3x-x\right|=-5x-2\end{cases}}\)
Để |3x - 3| = x => \(x\ge0\)
=> \(\orbr{\begin{cases}3x-3=x\\3x-3=-x\end{cases}\Rightarrow\orbr{\begin{cases}2x=3\\4x=3\end{cases}\Rightarrow}\orbr{\begin{cases}x=\frac{3}{2}\left(tm\right)\\x=\frac{3}{4}\left(tm\right)\end{cases}}}\)
Để |3x - 3| = - 5x - 2
=> \(-5x-2\ge0\Rightarrow x\le-\frac{2}{5}\)
=> \(\orbr{\begin{cases}3x-3=5x+2\\3x-3=-5x-2\end{cases}\Rightarrow\orbr{\begin{cases}-2x=5\\8x=1\end{cases}\Rightarrow}\orbr{\begin{cases}x=-\frac{5}{2}\left(\text{tm}\right)\\x=\frac{1}{8}\left(\text{loại}\right)\end{cases}}}\)
Vậy \(x\in\left\{\frac{-5}{2};\frac{3}{2};\frac{3}{4}\right\}\)
\(\left(-5-x\right)\left(3x+15\right)=\left(-2017\right)^{2008}\)
\(\Rightarrow-5\left(3x+15\right)-x\left(3x+15\right)=2017^{2008}\)
\(\Rightarrow-15x-75-3x^2+15x=2017^{2008}\)
\(\Rightarrow-75-3x^2=2017^{2008}\)
\(\Rightarrow3x^2=-75-2017^{2008}\)
\(3x^2\ge0\)
\(-75-2017^{2008}< 0\)
Vậy phương trình vô nghiệm